Humic acid improves water retention, maize growth, water use efficiency and economic benefits in coastal saline-alkali soils - Ge Li; Yuyang Shan; Weibo Nie; Yan Sun; Lijun Su; Weiyi Mu; Zhi Qu; Ting Yang (Agricultural Water Management)
Humic acid (HA) is an environmentally friendly and efficient soil amendment that plays a crucial role in the improving of saline-alkali soils. This study investigated the effects of HA on soil water retention, maize growth characteristics, water use efficiency (WUE), and economic benefits (∆NP) in coastal saline-alkali soil. Laboratory experiments tested five HA application rates (0, 1 ‰, 3 ‰, 5 ‰, and 7 ‰), examining their effects on soil infiltration, evaporation, and hydraulic parameters. Based on these findings, a three-year field experiment was conducted. During the maize growing seasons of 2019 and 2020, five HA application rates (H0: 0, H50: 50 kg ha−1, H150: 150 kg ha−1, H250: 250 kg ha−1, H350: 350 kg ha−1) were evaluated. In 2021, the improvement effects of HA were validated. The field experiment focused on the impacts of HA on soil water storage (SWS), desalination rate (RD), maize plant height (PH), leaf area index (LAI), aboveground dry matter (ADM), yield, WUE, and ∆NP. The results indicated that HA application increased cumulative infiltration by 0.83 %–9.92 %, extended the infiltration time required to reach the predetermined wetting front depth by 11.6 %–74.8 %, and reduced cumulative evaporation by 4.72 %–28.99 %. HA application rates showed a positive correlation with soil residual water content (θr) and saturated water content (θs), while exhibiting a negative correlation with saturated hydraulic conductivity (Ks). Appropriate HA application significantly enhanced SWS, RD, PH, LAI, ADM, yield, WUE, and ∆NP. Principal component analysis revealed that the H250 treatment in 2019 and the H50 treatment in 2020 achieved the highest comprehensive rankings. Furthermore, the function analysis of WUE and ∆NP identified the optimal HA application rates as 193.5 kg ha−1 and 182.3 kg ha−1, respectively. These findings provide a theoretical basis for the improving coastal saline-alkali soils effectively.